2023
DOI: 10.3389/fonc.2023.1191070
|View full text |Cite
|
Sign up to set email alerts
|

Little things with significant impact: miRNAs in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) has developed into one of the most lethal, aggressive, and malignant cancers worldwide. Although HCC treatment has improved in recent years, the incidence and lethality of HCC continue to increase yearly. Therefore, an in-depth study of the pathogenesis of HCC and the search for more reliable therapeutic targets are crucial to improving the survival quality of HCC patients. Currently, miRNAs have become one of the hotspots in life science research, which are widely present in liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 145 publications
0
6
0
Order By: Relevance
“…The combination of the two often has a synergistic effect and improves the prognosis of HCC patients. During the use of these systems for treatment, changes in miRNA expression profiles and levels in HCC patients may have important value in predicting drug efficacy, drug-related adverse events and prognosis[ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of the two often has a synergistic effect and improves the prognosis of HCC patients. During the use of these systems for treatment, changes in miRNA expression profiles and levels in HCC patients may have important value in predicting drug efficacy, drug-related adverse events and prognosis[ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chemotherapy induces the translation of circMRPS35, amplifying the malignant progression while simultaneously developing chemotherapeutic resistance. In another paper by Jiehan et al, miRNA-130b-3p expression was shown to be significantly increased in HCC and downregulated its expression by directly targeting (Homeobox protein Hox-A5), which further activated the PI3K/AKT/mTORpathway, thereby stimulating HCC cells to induce capillary tube formation, endothelial cell migration, and proliferation ( Li et al, 2023 ).…”
Section: Roles Of Microrna In the Livermentioning
confidence: 99%
“…At the same time, by similarly acting, specific related lncRNAs and sncRNAs have been demonstrated to be actively involved in cancer-related chemoresistance processes, representing potential tools to optimize therapeutic approaches even in HCC management [72]. Based on this, in the last few decades, various encouraging results have emerged from the dramatic amount of research exploring potential ncRNA HCC-therapeutic targets [182,183].…”
Section: Potential Ncrna Applications In Hcc Treatment: a Close-to-ex...mentioning
confidence: 99%